Water quality monitoring using remote sensing, Lower Manyame Sub-catchment, Zimbabwe. Issue 6 (3rd June 2022) - Muhoyi, H.; Gumindoga, W.; Mhizha, A.; Misi, S. N.; Nondo, N.
Abstract: The Lower Manyame Sub-catchment (LMS) is one of the most heavily polluted in Zimbabwe. Its waters are valuable for irrigation, domestic and industrial purposes. LMS has serious eutrophication problems emanating from human activities within it, and lakes Manyame and Chivero upstream. Data collected from October 2018 to April 2019 were used to test an integrated methodology based on field measurements and remote sensing. This study illustrates the production of multitemporal spatialised maps of total suspended solids (TSS), chemical oxygen demand (COD), total nitrogen (TN) and total phosphorus (TP) concentrations from satellite data acquired from Sentinel-2. The analysis confirmed the pollution (eutrophic and organic matter) status of LMS water, for the period considered by this research. As a result, careful land planning must be done through the joint operation of local authorities, regional agencies and regional institutions, since Manyame River is a tributary of the Zambezi River (a transboundary river). HIGHLIGHTS: Lower Manyame Sub-catchment rivers are vulnerable to nutrient loading. This research established high phosphorous loading in the sub-catchment. Field data and Sentinel-2 data analysis confirmed pollution levels in LMS. High-resolution satellite data can be used to monitor surface water quality. Graphical Abstract